2016
DOI: 10.1021/acs.langmuir.6b01656
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Characterization of Preferential Gas Adsorption at the Graphene–Water Interface

Abstract: The contact of water with graphene is of fundamental importance and of great interest for numerous promising applications, but how graphene interacts with water remains unclear. Here we used atomic force microscopy (AFM) to investigate hydrophilic mica substrates with some regions covered by mechanically exfoliated graphene layers in water. In water containing air gas close to the saturation concentration (within ∼40%), cap-shaped nanostructures (or interfacial nanobubbles) and ordered-stripe domains were obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 50 publications
4
26
0
Order By: Relevance
“…5−16 Moreover, different stripe widths ranging from 2 to 6 nm have been reported in literature. [5][6][7]12,15 Similarly, contradicting information is available on the solvation structure on top of the stripes. 17,19 Although some groups have ascribed the stripes to airborne contaminations 11−14 or to the formation of methanol−water nanostructures, 18 others have explained the origin of the stripes by intercalation and different interplanar stackings 12 or the assembly of dissolved nitrogen molecules at the graphite/graphene−water interface.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5−16 Moreover, different stripe widths ranging from 2 to 6 nm have been reported in literature. [5][6][7]12,15 Similarly, contradicting information is available on the solvation structure on top of the stripes. 17,19 Although some groups have ascribed the stripes to airborne contaminations 11−14 or to the formation of methanol−water nanostructures, 18 others have explained the origin of the stripes by intercalation and different interplanar stackings 12 or the assembly of dissolved nitrogen molecules at the graphite/graphene−water interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…17,19 Although some groups have ascribed the stripes to airborne contaminations 11−14 or to the formation of methanol−water nanostructures, 18 others have explained the origin of the stripes by intercalation and different interplanar stackings 12 or the assembly of dissolved nitrogen molecules at the graphite/graphene−water interface. [5][6][7][8][9]17 The interpretation of the stripes being composed of nitrogen has received considerable attention because of its potential impact for explaining the long-range nature of the hydrophobic interaction. 17,20,21 In the view of this discussion, it becomes increasingly relevant to shed light onto the structural details of the stripes and, in particular, to clarify the chemical nature of the constituents.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the roles of dissolved N 2 and O 2 molecules in lipid bilayers have never been investigated experimentally. Even though the saturation concentrations of dissolved air gases in water are very low (molecular ratios are ≈10 ppm for N 2 and ≈5 ppm for O 2 ), it has recently been found that dissolved air gas has a high tendency to accumulate at hydrophobic surfaces . Thus, dissolved N 2 and O 2 molecules may also segregate at the hydrophobic cores of lipid bilayers, affecting the properties of the bilayers.…”
Section: Introductionmentioning
confidence: 99%
“…The uneven distribution of SA particles on the GWI indicates a non-uniformed interfacial property of the graphene surface in our experiments. We do not have a good explanation for this phenomenon, whereas possible causes might include heterogeneous hydrophilicity, adsorbates contamination, or more complicated graphene–water interfacial interactions on the graphene surface 45,46 . Taking advantage of the different distribution patterns of SA particles on the GWI and AWI, we could roughly separate the dataset in two groups.…”
Section: Discussionmentioning
confidence: 92%